Chatbots development with Amazon Lex. (Packt Publishing, 2023)
Amazon Lex, a fully-controlled AI service, has sophisticated natural language models to create, develop, test, and deploy chatbots (conversational interfaces) in applications. Amazon Web Service (AWS) provides AWS Lambda, a serverless computing service without provisioning or managing servers. The course begins with an exhaustive overview of the fundamentals of AWS for chatbots, training chatbot development with deep learning. Afterward, we will delve into the characteristics of AWS and its notable functionalities. Following this, we will embark on constructing a chatbot for hotel booking utilizing Amazon Lex. Subsequently, we will acquire the skills to establish an AWS Lambda function and establish its connection with Amazon Lex. Then, we will cover the concepts of chatbot backend development for AWS Lex and AWS Lambda. We will further advance to integrate the chatbot with Twilio and learn to use the AWS Software Development Kit. Website integration of AWS Lex chatbot and implementing response cards with chatbots is the final concept that we will explore in the course. Upon completing this course, you will relate concepts and theories for chatbots in various domains, gain extensive understanding, and learn to implement AWS Lex and AWS Lambda for building real-world chatbots. You will independently build customized chatbots with AWS Lex and AWS Lambda and integrate your chatbots with WhatsApp, messaging apps, and websites. What You Will Learn Learn the fundamentals of Amazon Web Services (AWS) Gain hands-on chatbot development with Amazon Lex and Amazon Lambda Explore web-based Amazon Web Services chatbot development Run code on AWS Lambda without provisioning or managing servers Learn practical usage of Twilio and its integration with AWS for chatbots Explore the functionality of Amazon Lex for chatbot development Audience This course is tailored for individuals interested in AWS and applying AWS Lex and AWS Lambda for chatbot development. This course will benefit individuals interested in building customized chatbots for their applications--AI practitioners, chatbot developers, research scholars, data scientists, and so on. About The Author AI Sciences: AI Sciences are experts, PhDs, and artificial intelligence practitioners, including computer science, machine learning, and Statistics. Some work in big companies such as Amazon, Google, Facebook, Microsoft, KPMG, BCG, and IBM. AI sciences produce a series of courses dedicated to beginners and newcomers on techniques and methods of machine learning, statistics, artificial intelligence, and data science. They aim to help those who wish to understand techniques more easily and start with less theory and less extended reading. Today, they publish more comprehensive courses on specific topics for wider audiences. Their courses have successfully helped more than 100,000 students master AI and data science.